2021
DOI: 10.3390/molecules26082319
|View full text |Cite
|
Sign up to set email alerts
|

The Skeletal Effects of Tanshinones: A Review

Abstract: Background: Osteoporosis results from excessive bone resorption and reduced bone formation, triggered by sex hormone deficiency, oxidative stress and inflammation. Tanshinones are a class of lipophilic phenanthrene compounds found in the roots of Salvia miltiorrhiza with antioxidant and anti-inflammatory activities, which contribute to its anti-osteoporosis effects. This systematic review aims to provide an overview of the skeletal beneficial effects of tanshinones. Methods: A systematic literature search was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…The study confirmed that tanshinones can exert bone remodeling and bone protective effects by inhibiting osteoclastogenesis/bone resorption and promoting osteoblastogenesis/bone formation [70]. Tanshinones isolated from Danshen were able to ameliorate peroxidative damage, adjust the level of serum superoxide dismutase (SOD) and malonaldehyde (MDA), and inhibit the secretion of IL-6 and TNF-α, thus attenuating rheumatoid arthritis (RA) [71].…”
Section: Effect On Rheumatoid Arthritismentioning
confidence: 84%
“…The study confirmed that tanshinones can exert bone remodeling and bone protective effects by inhibiting osteoclastogenesis/bone resorption and promoting osteoblastogenesis/bone formation [70]. Tanshinones isolated from Danshen were able to ameliorate peroxidative damage, adjust the level of serum superoxide dismutase (SOD) and malonaldehyde (MDA), and inhibit the secretion of IL-6 and TNF-α, thus attenuating rheumatoid arthritis (RA) [71].…”
Section: Effect On Rheumatoid Arthritismentioning
confidence: 84%
“…24,26 Codonopsis Radix (Danshen) is a common hemorheological medicine containing tanshinone, which has antioxidant and anti-inflammatory effects and excellent efficacy in removing blood stasis, relieving pain, and improving microcirculation and blood flow to injured spinal cord tissues. 25,27 All the TCM in the prescription can be used in tandem to address both symptoms and root problems. To stimulate blood circulation, remove blood stasis, and dispel wind and dehumidify, the liver, spleen, and kidney can be replanted concurrently.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the combination of Chaenomeles speciosa (Mugua) reduces wind and moisture while treating the tip simultaneously. Studies have shown that, 2428 Chaenomeles Speciosa (Mugua), Codonopsis Radix (Danshen), and turmeric (Jianghuang) all serve major anti-inflammatory roles. Chaenomeles speciosa (Mugua) has been widely employed in the clinical treatment of inflammatory illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Several recommendations for future studies are suggested. Firstly, various plant extracts and their isolated bioactive compounds have been extensively demonstrated by researchers to exert potent bone-protecting properties [ 85 , 86 , 87 , 88 , 89 , 90 ], which could be introduced into CPC to improve its physical, mechanical, and osteogenic effects. Secondly, a three-dimensional osteoblast-osteoclast co-culture system mimicking the skeletal microenvironment in humans could be used to investigate the properties of CPC after the reinforcement using biological materials [ 91 , 92 ].…”
Section: Perspectivesmentioning
confidence: 99%